Management of rare movement disorders in Europe: outcome of surveys of the European Reference Network for Rare Neurological Diseases. (19th June 2020) - Painous, C.; van Os, N. J. H.; Delamarre, A.; Michailoviene, I.; Marti, M. J.; van de Warrenburg, B. P.; Meissner, W. G.; Utkus, A.; Reinhard, C.; Graessner, H.; Tijssen, M. A.
Abstract : Background and purpose: The diagnosis of rare movement disorders is difficult and specific management programmes are not well defined. Thus, in order to capture and assess care needs, the European Reference Network for Rare Neurological Diseases has performed an explorative care need survey across all European Union (EU) countries. Methods: This is a multicentre, cross‐sectional study. A survey about the management of different rare movement disorders (group 1, dystonia, paroxysmal dyskinesia and neurodegeneration with brain iron accumulation; group 2, ataxias and hereditary spastic paraparesis; group 3, atypical parkinsonism; group 4, choreas) was sent to an expert in each group of disorders from each EU country. Results: Some EU countries claimed for an increase of teaching courses. Genetic testing was not readily available in a significant number of countries. Regarding management, patients' accessibility to tertiary hospitals, to experts and to multidisciplinary teams was unequal between countries and groups of diseases. The availability of therapeutic options, such as botulinum toxin or more invasive treatments like deep brain stimulation, was limited in some countries. Conclusions: The management of these conditions in EU countries is unequal. The survey provides evidence that a European care‐focused network that is able to address the unmet rare neurological disease care needs and inequalities is highly warranted.